Combined mutation screening of NKX2-5, GATA4, and TBX5 in congenital heart disease: multiple heterozygosity and novel mutations - Granados-Riveron, Javier T.; Pope, Mark; Bu'Lock, Frances A.; Thornborough, Christopher; Eason, Jacqueline; Setchfield, Kerry; Ketley, Ami; Kirk, Edwin P.; Fatkin, Diane; Feneley, Michael P.; Harvey, Richard P.; Brook, David (Wiley, 2012)
Background: Variants of several genes encoding transcription modulators, signal transduction, and structural proteins are known to cause Mendelian congenital heart disease (CHD). NKX2-5 and GATA4 were the first CHD-causing genes identified by linkage analysis in large affected families. Mutations of TBX5 cause Holt–Oram syndrome, which includes CHD as a clinical feature. All three genes have a well-established role in cardiac development.